Shortened insulin analogues: marked changes in biological activity resulting from replacement of TyrB26 and N-methylation of peptide bonds in the C-terminus of the B-chain - Záková, Lenka; Barth, Tomislav; Jirácek, Jirí; Barthová, Jana; Zórad, Stefan (Biochemistry, 2004)
The role of three highly conserved insulin residues PheB24, PheB25, and TyrB26 was studied to better understand the subtleties of the structure-function relationship between insulin and its receptor. Ten shortened insulin analogues with modifications in the beta-strand of the B-chain were synthesized by trypsin-catalyzed coupling of des-octapeptide (B23-B30)-insulin with synthetic peptides. Insulin analogues with a single amino acid substitution in the position B26 and/or single N-methylation of the peptide bond at various positions were all shortened in the C-terminus of the B-chain by four amino acids. The effect of modifications was followed by two types of in vitro assays, i.e., by the binding to the receptor of rat adipose plasma membranes and by the stimulation of the glucose transport into the isolated rat adipocytes. From our results, we can deduce several conclusions: (i) the replacement of tyrosine in the position B26 by phenylalanine has no significant effect on the binding affinity and the stimulation of the glucose transport of shortened analogues, whereas the replacement of TyrB26 by histidine affects the potency highly positively; [HisB26]-des-tetrapeptide (B27-B30)-insulin-B26-amide and [NMeHisB26]-des-tetrapeptide (B27-B30)-insulin-B26-amide show binding affinity 529 and 5250%, respectively, of that of human insulin; (ii) N-methylation of the B24-B25 peptide bond exhibits a disruptive effect on the potency of analogues in both in vitro studies regardless the presence of amino acid in the position B26; (iii) N-methylation of the B23-B24 peptide bond markedly reduces the binding affinity and the glucose transport of respective analogue [NMePheB24]-des-tetrapeptide (B27-B30)-insulin-B26-amide.
Keywords: vodíková vazba; Amino Acid Substitution; Deoxyglucose; Humans; deoxyglukosa; Tyrosine; podjednotky proteinů; Protein Binding; krysa rodu Rattus; lidé; Recombinant Proteins; zvířata; receptor inzulinu; Methylation; potkani Wistar; Swine; Peptide Fragments; rekombinantní proteiny; biologický transport; Rats, Wistar; metylace; Male; substituce aminokyselin; Insulin; Protein Subunits; Phenylalanine; vazba proteinů; Hydrogen Bonding; peptidové fragmenty; Receptor, Insulin; Rats; Animals; fenylalanin; mužské pohlaví; terciární struktura proteinů; Protein Structure, Tertiary; tyrosin; prasata; Biological Transport; inzulin